Political Economy and Neoclassical Theory – Facing the Trial of Time - Mihailov, Penyu (Research Papers, 2015)
The object of this paper is the unity and diversity between political economy and the neo classical theory. In the opinion of the author, these are two branches of economic knowledge. The author declares on objection against the view that the neo-classical theory is universal and irreproachable. Life has proved for more complicated than we have imagined it.The paper discuss questions such as „What economic theory do we need?“, issues concerning the interference of the state; theoretical and empirical knowledge; neo-liberal ideology and the economic crisis; pluralism in teaching economic theory.JEL:A10, A11, A13, B0, B10, B41
Keywords: Economics; Economic theory; Neoclassical theory; Economic practice; Financial and economic crisis; Criticism to neoliberal economy; Pluralism in economic education.; Political economy